Zavarovalna izkopavanja v Novem mestu in okolici - Šribar, Vinko (Arheološki vestnik, 1959)
During the years 1954 and 1955 there were at Novo mesto four excavations of protective character: the La Tene necropolis on the Marof, the Roman burying[1]place in the Bele garden, the urn-grave in the “Klemenčič Fields” on the Marof, and the Roman burning cemetery in the vicinity of the village Brod near Šmihel. The material from the La Tene necropolis on the Kapitelj Marof represents our earliest La Tene stage. With the exception of two vessels that are by their form and their execution of La Tene character the forms of all the other vessels are based on the Hallstatt tradition. In the burying-place in the Bele garden we distinguish two kinds of material: ours and that excavated in 1902. This material represents a temporal and cultural continuity from the latest phase of the Middle La Tene age to the 2nd, century A.D . In the material belonging to the Roman period we see a definite continuation of the La Tene tradition so that we can suppose that we have here to do with the carriers of the same ethnic group. In the “Klemenčič Fields” we have excavated only one urn-grave which be[1]longs to the cultural group comprising the older Vače, Mokronog, Ljubljana — Trg revolucije etc, at the time for which the doubleloped, arch- shaped fibula is characteristic. From the Roman burnt graves at the village Brod there is not preserved any ceramic vessel nor any article the time of which could be determined. However, owing to the complete affinity between the construction of the grave formed like a box and the grave number 1 it is very likely that the times of their origin are lying close together.